1992
DOI: 10.1300/j010v17n01_06
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Fmaily-Centered Case Management Approach

Abstract: Two urban programs of family-centered case management services were established for families of children with both a developmental disability and a chronic health condition. These are children who present significant caregiving demands due to the long-term and severe nature of their disabilities. Thirty-two mothers were interviewed within the family's first month in the project and reinterviewed approximately one year later. The results indicate that more families received respite care, nursing services, train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 5 publications
0
16
0
2
Order By: Relevance
“…A study carried out by Marcenko & Smith (1992) to determine the efficacy of a case management programme found that case management assists parents in accessing, coordinating and monitoring services. This is especially important for parents whose child's care needs are changing over time.…”
Section: Case Managementmentioning
confidence: 99%
“…A study carried out by Marcenko & Smith (1992) to determine the efficacy of a case management programme found that case management assists parents in accessing, coordinating and monitoring services. This is especially important for parents whose child's care needs are changing over time.…”
Section: Case Managementmentioning
confidence: 99%
“…There is a small body of evidence on the effects of having a key worker (e.g. Beresford, 1995; Glendinning, 1986; Koren and others, 1997; Marcenko and Smith, 1992; Mukherjee and others, 1999; Presler, 1998; Sloper and Turner, 1992; Tait and Dejnega, 2001). Liabo and others (2001), in a review of the evidence, concluded that if families receive a key worker service, their overall quality of life is improved, they have better relationships with services, quicker access to services and benefits and reduced levels of stress; parents had good personal relationships with their key workers; key workers were satisfied with the role and believed that it made a positive difference to children and families and a key worker who works for a service appears to be more able to access necessary resources than someone who is an independent advocate.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of the experience provides insight into the dynamics of the prenatal attachment process in these pregnancies-pregnancies in which women are provided knowledge of nonlethal abnormalities and are faced with the challenge of becoming mothers to infants with abnormalities. This is important because children with disabilities often demand significant caregiving due to the possibly severe and long-term nature of their disabilities (Marcenko & Smith, 1992;McCubbin, 1989). It has been found that mothers of disabled infants have lower levels of maternal attachment behaviors in the neonatal period (Capuzzi, 1989) and that there is an increased incidence of child abuse of children with disabilities (American Academy of Pediatrics, Committee on Child Abuse and Neglect, and Committee on Children with Disabilities, 2001; National Society for the Prevention of Cruelty to Children, 2003;Stanton, Seidl, Pillitteri, & Smith, 1994).…”
mentioning
confidence: 99%